Comparison of vaginal microbiota in gynecologic cancer patients pre‐ and post‐radiation therapy and healthy women. (1st April 2020) - Tsementzi, Despina; Pena‐Gonzalez, Angela; Bai, Jinbing; Hu, Yi‐Juan; Patel, Pretesh; Shelton, Joseph; Dolan, Mary; Arluck, Jessica; Khanna, Namita; Conrad, Lesley; Scott, Isabelle; Eng, Tony Y.; et al.
Abstract: Background: While the importance of commensal microbes in vaginal health is well appreciated, little is known about the effects of gynecological cancer (GynCa) and radiation therapy (RT) on the vaginal microbiome (VM) of postmenopausal women. Methods: We studied women with GynCa, pre‐ (N = 65) and post‐RT (N = 25) and a group of healthy controls (N = 67) by sequencing the V4 region of the 16S rRNA gene from vaginal swabs and compared the diversity and composition of VMs between the three groups accounting for potential confounding factors in multivariate analysis of variance. Results: Comparisons of cancer vs healthy groups revealed that Lactobacillus and Bifidobacterium have significantly higher relative abundance in the healthy group, while the cancer group was enriched in 16 phylogroups associated with bacterial vaginosis (BV) and inflammation, including Sneathia, Prevotella, Peptoniphilus, Fusobacterium, Anaerococcus, Dialister, Moryella, and Peptostreptococcus . In our sample, RT affected the α‐diversity and correlated with higher abundance of typically rare VM species, including several members of the Lacnospiraceae family, a taxon previously linked to vaginal dysbiosis. In addition to cancer and treatment modalities, age and vaginal pH were identified as significant parameters that structure the VM. Conclusions: This is among the first reports identifying VM changes among postmenopausal women with cancer. RT alone seems to affect several phylogroups (12 bacterial genera), while gynecological cancer and its treatment modalities are associated with even greater significant shifts in the vaginal microbiota including the enrichment of opportunistic bacterial pathogens, which warrants further attention. Abstract : Vaginal microbial communities in postmenopausal women undergoing gynecologic cancer treatments have small but detectable differences compared to healthy controls, including higher diversity and abundance of opportunistic bacterial pathogens. Radiation therapy alone seems to affect several phylogroups (12 bacterial genera), while gynecological cancer and its treatment modalities (surgery and chemotherapy) are associated with even greater significant shifts in the vaginal microbiota including the enrichment of opportunistic bacterial pathogens, which warrants further attention.